Research on the Development of China’s New Energy Vehicle Industry in the New Economic Environment - Wang, Pengyan; Wang, Zian; Yang, Chenglu (Transactions on Economics, Business and Management Research, 2024)
As China’s new energy vehicle industry continues to grow, it is becoming more and more important to the country’s economic development. After comprehensively considering the in-depth research results of many scholars on the relationship between new energy vehicles and China’s economy, combined with the current stage characteristics of China’s new energy industry and the overall economic development, this paper aims to comprehensively and systematically analyze the important role of this industry in China’s economic development, as well as the challenges and opportunities it faces. China’s new energy automobile industry has had a significant positive impact on many aspects of China’s real economy, export economy and low-carbon economy. However, the development of this industry is also affected and restricted by many factors. It also drives the development of various industries at the same time. It currently acts as a practical catalyst for China’s economic growth. Even though the new energy vehicle sector will encounter several obstacles in the future, overall, the sector is trending forward. It will also have a long-lasting favorable effect on China’s economy going forward.